From 9c04ffcfa12e80434502b826c240ecc3baf95820 Mon Sep 17 00:00:00 2001 From: Holden Rohrer Date: Sun, 20 Sep 2020 17:53:32 -0400 Subject: best attempt at hw 2 of Houdre --- houdre/hw2.tex | 142 +++++++++++++++++++++++++++++++++++++++++++++++++++++++++ 1 file changed, 142 insertions(+) create mode 100644 houdre/hw2.tex (limited to 'houdre') diff --git a/houdre/hw2.tex b/houdre/hw2.tex new file mode 100644 index 0000000..7bd11b4 --- /dev/null +++ b/houdre/hw2.tex @@ -0,0 +1,142 @@ +\newfam\rsfs +\newfam\bbold +\def\scr#1{{\fam\rsfs #1}} +\def\bb#1{{\fam\bbold #1}} +\let\oldcal\cal +\def\cal#1{{\oldcal #1}} +\font\rsfsten=rsfs10 +\font\rsfssev=rsfs7 +\font\rsfsfiv=rsfs5 +\textfont\rsfs=\rsfsten +\scriptfont\rsfs=\rsfssev +\scriptscriptfont\rsfs=\rsfsfiv +\font\bbten=msbm10 +\font\bbsev=msbm7 +\font\bbfiv=msbm5 +\textfont\bbold=\bbten +\scriptfont\bbold=\bbsev +\scriptscriptfont\bbold=\bbfiv + +\def\Pr{\bb P} +\def\E{\bb E} +\newcount\qnum +\def\q{\afterassignment\qq\qnum=} +\def\qq{\bigskip\goodbreak\noindent{\bf \number\qnum)}\smallskip} +\def\infsum#1#2{\sum_{#1=#2}^\infty} +\def\fr#1#2{{#1\over #2}} + +\q1 + +$\E(X(X-1)\cdots (X-k)) = \E(g(X))$ where $g(x) = {x!\over(x-(k+1))!}.$ + +This gives an expected value of $$\infsum x0 g(x){\lambda^x\over x!} += \infsum x{k+1} {\lambda^x\over (x-(k+1))!} = +\lambda^{k+1}\infsum x{k+1} {\lambda^{x-(k+1)}\over (x-(k+1))!} += \lambda^{k+1}\infsum x0 {\lambda^x\over x!} += \lambda^{k+1}.$$ +The second transformation is possible because $g(x)$ is zero for +$x\in{0,1,\ldots,k}$. +This last sum is equal to one because the Poisson distribution is a +probability mass function, and this is a Poisson distribution. + +\q2 + +If a head is flipped (with probability $p$), only $r-1$ heads remain to +flip, so the mean time to end is $m(r-1).$ +If a tail is flipped (with probability $q=1-p$), the mean remaining +number of flips remains the same at $m(r)$. +However, this adds one to the count either way, so $$m(r) = 1+p(m(r-1)) ++ q(m(r)).$$ +Turning this into a difference equation gives $$pm_{r+1} - pm_r = 1.$$ +The complementary equation gives a solution of $c_1$ because $\theta - +1$ has only the root of $1$, so $x_n = c_1\cdot 1$ (but, since the +series starts at 0 tosses for 0 heads, $c_1=0$). +The particular equation can be found to be $r/p$, so the general +equation is $r/p.$ This is the mean number of tosses. + +\q4 + +$\infsum k1 k^\alpha$ converges if $\alpha < -1.$ With +$$c\infsum k1 k^\alpha = 1\iff c = {1\over \infsum k1 k^\alpha},$$ +this function is a probability mass function because it will by +definition have the sum over its domain be one. + +\q5 + +The geometric distribution is $pq^{k-1}$. +$$\Pr(X > m+n | X > m) = {\infsum x{m+n} pq^{x-1}\over \infsum xm +pq^{x-1}} = {q^{m+n}\over q^m} = q^n = \Pr(X > n).$$ +These sums converge to these values because $\infsum x0 pq^{x-1} = 1,$ +and $q^k$ can be factored out if the sum doesn't start at zero. + +From this definition, $\Pr(X > m+n | X > m) = \Pr(X > n),$ the +geometric distribution can be derived, so because iff this is true, the +distribution is geometric, the geometric is the only distribution for +which this is true. +$${\Pr(X > m+n\cap X > m)\over \Pr(X > m)} = \Pr(X > n) +\to \Pr(X > n)\Pr(X > m) = \Pr(X > m+n)$$ +$$\to \Pr(X = n)\Pr(X = m) = \Pr(X = m+n) +\to \Pr(X = n)\Pr(X = 1) = \Pr(X = n+1) +\to a_{n+1} = qa_n.$$ +The only probability mass distribution that follows this form is the +geometric distribution. + +\q6 + +$$\infsum k0 \Pr(N > k) = \infsum k1 \infsum jk \Pr(N = j) += \infsum j1 \sum_{k=1}^j \Pr(N=k) = \infsum j1 j\Pr(N=j).$$ + +Because this last expression is the definition of $\E(n)$, this is true. + +Throwing this fair die gives $3^n$ possible patterns which have been +thrown. Of two items, the number of possible patterns is $2^n$. Of one +item, the number of possible patterns is $1^n$. Using inclusion-% +exclusion, there are ${3\choose 2} = 3$ pairs of sides, so there are +$3*2^n$ patterns without all colors. But this double-counts one single +side showing up twice in two pairs (both RB and GB consider BBBBB to be +a possible pattern), so the real number is $3*(2^n-1).$ This gives a +probability of $\Pr = {2^n - 1\over 3^{n-1}}.$ + +Using the formula $n\sum_{k=1}^n \fr1k$ to be proved in question seven, +the expected value is $11\over2$ because $3*(1+\fr12+\fr13) = +3*{11\over6} = 11\over2$. + +\q7 + +Let the coupon collector be attempting to collect $n$ coupons. The mean +time to 1 coupon is one collection. After $k$ coupons have been +collected, the probability of choosing a new coupon is ${n-k\over n}.$ +This gives a mean time to the next new coupon which can be calculated by +a partition. $m(k+1) = (m(k)+1){n-k\over n} + (m(k+1)+1){k\over n} \to +{n-k\over n}m(k+1) = m(k){n-k\over n} + 1 \to m(k+1) = \fr n{n-k}+m(k).$ +$m(n) = \sum_{k=1}^n \fr n{n-k} = \sum_{k=1}^n \fr nk = n\sum_{k=1}^n +\fr1k.$ + +The probability that the first $n$ coupons do not form a complete set of +$k$ coupons is calculable as $$\sum_{j=1}^{k-1} (-1)^{k-j}{k\choose k-j} +{(k-j)^n\over k^n}.$$ +This is accurate because this corresponds to the probability of the +union (calculated using inclusion-exclusion) of all subsets of $k-1$ +possible coupons (the largest possible group that doesn't form a +complete set). + +\q9 + +Zero heads in a row is achieved immediately---zero tosses, so the mean +number of tosses is zero: $m(0) = 0.$ +Given that flipping $n$ heads in a row happens after mean tosses $m(n)$, +$n+1$ heads in a row has probability +$m(n+1) = p(m(n)+1) + q(m(n)+m(n+1)+1).$ +The first case is if one more head is flipped---this has a probability +$p$ of happening and requires, on average, the mean tosses of $n$ heads +in a row plus one for the head. +The second case is if one more tail is flipped---this has a probability +of $q=1-p$ and requires 1 more flip for the tail and $m(n+1)$ more +expected flips after the failure, which will come, on average after +$m(n)$ flips. + +Solving this as a difference equation gives $(1-q = p)m_{n+1} - m_n - +1 = 0.$ Let $k = 1/p.$ A particular solution is $m_n = {k(k^n-1)\over +k-1}.$ A complementary solution is $c_1k^{n-1},$ so a general solution +is $m_n = c_1k^{n-1} + {k(k^n-1)\over k-1}.$ +\bye -- cgit